2004
DOI: 10.1123/ijsnem.14.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutrition Knowledge and Dietary Recommendations by Coaches of Adolescent Brazilian Athletes

Abstract: The objectives of this study were to describe the dietary practices recommended by coaches working with adolescent athletes and to assess their nutritional knowledge. During a regional competition in the state of Sao Paulo, Brazil, 55 coaches were interviewed. These coaches represented 22 cities with athletes enrolled in Olympic gymnastics, tennis, swimming, and judo events. A 3-section questionnaire was used to obtain data on demographic characteristics, dietary recommendations, and nutrition knowledge. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 33 publications
3
52
2
5
Order By: Relevance
“…Rosenbloom et al 8 also noted that athletes avoid carbohydrates when trying to lose weight. In another study 25 the belief that pineapple helps to "burn body fat" was common among coaches, and the authors highlighted the risk of propagating this information among athletes. Protein overvaluation was also observed by Almeida & Soares 26 , who analyzed the dietary profile of adolescent volleyball players.…”
Section: Discussionmentioning
confidence: 99%
“…Rosenbloom et al 8 also noted that athletes avoid carbohydrates when trying to lose weight. In another study 25 the belief that pineapple helps to "burn body fat" was common among coaches, and the authors highlighted the risk of propagating this information among athletes. Protein overvaluation was also observed by Almeida & Soares 26 , who analyzed the dietary profile of adolescent volleyball players.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study on nutritional knowledge and behavior of athletes in Khorramabad; therefore, follow-up studies of this kind can be considered as a basis for evaluation of developing nutritional programs in different periods. Evaluating nutritional knowledge and recommendations of 55 trainers, Juzwiak et al [19] observed that Brazilian trainers responded correctly to 70% of nutritional knowledge inventory. Nevertheless, no difference was found in nutritional knowledge of trainers of different sports (gymnastics, judo, swimming and tennis) (p = 0.61).…”
Section: Discussionmentioning
confidence: 99%
“…Desse modo, apesar de não existirem mecanismos legais que incluam a nutrição no currículo de educação física das instituições, já que esta não é exigência para atuação profissional, a nutrição básica está presente em parte dos cursos de educação física, visto que tais conhecimentos mínimos são de fundamental importância para profissionais cujo trabalho tem relação com a promoção da saúde, prevenção de doenças ou recuperação da saúde (BOOG, 1999;JUZWIAK;ANCOLA-LOPEZ, 2004). No caso da Nutrição Esportiva, uma hipótese para explicar um menor rendimento dos instrutores em questões relativas a essa área do conhecimento, poderia ser o fato da não realização de cursos ou disciplinas na área de nutrição esportiva, apesar destes terem relatado utilizar fontes sobre informações da ciência da nutrição que oferecem maior confiabilidade, como palestras, seminários e cursos.…”
Section: Discussionunclassified
“…Considerando aqui as academias como conglomerados e baseando-se numa prevalência de 37,2% de baixo conhecimento em nutrição (ZINN, 2004;JUZWIAK;ANCOLA-LOPEZ, 2004), e ainda assumindo um erro de dois pontos percentuais, nível de confiança de 95% e 20% de possíveis perdas e recusas, calculou-se necessá-rio estudar 39 academias. Destas, foi realizada amostra estratificada proporcional por região.…”
Section: Cálculo Amostralunclassified